A STUDY ON THE ANALYTICAL FRAMEWORK OF KAZAKHSTAN’S MEDIA COVERAGE OF THE "BELT AND ROAD INITIATIVE" - Li Yuran; Zhurtbay Nazym (World Scientific Reports, 2025)
This study is dedicated to the analysis of coverage of the Belt and Road initiative in Kazakh media. The aim of the work is to identify features of information discourse, key topics, and rhetorical strategies used in different types of media. The analysis is based on methods of discourse analysis, content analysis, and comparative analysis of sources. Special attention is given to differences between Russian- and Kazakh-language publications, as well as their presentation in state-owned and independent media. Results of the study were systematized using PESTLE analysis, which allowed us to evaluate political, economic, social, technological, and legal aspects of media representation of the initiative. The conclusion is drawn from the analysis of the predominance of official and positive rhetoric in the media coverage of transnational projects, as well as the lack of critical and legal assessments. It is suggested that a more balanced and multifaceted approach to the reporting of these projects is needed